Metformin inhibits the production of reactive oxygen species from NADH: Ubiquinone oxidoreductase to limit induction of interleukin-1Î² (IL-1Î²) and boosts interleukin-10 (IL-10) in lipopolysaccharide (LPS)-activated macrophages - O'NEILL, LUKE (My University, 2015)
Background: The antidiabetic drug and mitochondrial NADH:ubiquinone oxidoreductase (complex I) inhibitor metformin has anti-inflammatory activity. Results: Complex I inhibition decreases LPS-induced IL-1β and boosts IL-10. Mitochondrial ROS may be a signal driving LPS-induced IL-1β. Conclusion: Complex I has a role in the induction of cytokines by LPS. Significance: This study provides insight into the anti-inflammatory action of metformin and reveals a role for complex I dysfunction in inflammatory signaling
Keywords: antidiabetic drug; antidiabetic drug